Summing up

Calculus Level 3

n = 1 n 4 ( n + 1 ) ! = ? \large\displaystyle\sum_{n=1}^{\infty}\frac{n^4}{(n+1)!} = \,?

Find the value of the closed form of the above series to 3 decimal places.


The answer is 9.873.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Marco Brezzi
Aug 18, 2017

S = n = 1 n 4 ( n + 1 ) ! = n = 1 n 4 n 2 + n 2 1 + 1 ( n + 1 ) ! = n = 1 n 2 ( n + 1 ) ( n 1 ) ( n + 1 ) ! + n = 1 ( n + 1 ) ( n 1 ) ( n + 1 ) ! + n = 1 1 ( n + 1 ) ! = n = 1 n ( n 1 ) ( n 1 ) ! + n = 1 n 1 n ! + e 2 = n = 2 n ( n 1 ) ( n 1 ) ! + n = 1 [ 1 ( n 1 ) ! 1 n ! ] + e 2 = n = 2 [ n ( n 2 ) ! ] + 1 + e 2 c c c c c c c c c c c c c c c c c c c c c by Telescoping series sum = n = 2 [ n 2 + 2 ( n 2 ) ! ] + e 1 = n = 2 n 2 ( n 2 ) ! + n = 2 2 ( n 2 ) ! + e 1 = n = 3 n 2 ( n 2 ) ! + 2 e + e 1 = n = 3 1 ( n 3 ) ! + 3 e 1 = 4 e 1 9.873 \begin{aligned} S&=\sum_{n=1}^{\infty} \dfrac{n^4}{(n+1)!}\\ &=\sum_{n=1}^{\infty} \dfrac{n^4-n^2+n^2-1+1}{(n+1)!}\\ &=\sum_{n=1}^{\infty} \dfrac{n^2(n+1)(n-1)}{(n+1)!}+\sum_{n=1}^{\infty}\dfrac{(n+1)(n-1)}{(n+1)!}+\sum_{n=1}^{\infty}\dfrac{1}{(n+1)!}\\ &=\sum_{\color{#3D99F6}n=1}^{\infty}\dfrac{n(n-1)}{(n-1)!}+\sum_{n=1}^{\infty}\dfrac{n-1}{n!}+e-2\\ &=\sum_{\color{#D61F06}n=2}^{\infty}\dfrac{n(n-1)}{(n-1)!}+\mathbin{\color{#3D99F6}\sum_{n=1}^{\infty}\left[\dfrac{1}{(n-1)!}-\dfrac{1}{n!}\right]}+e-2\\ &=\sum_{n=2}^{\infty}\left[\dfrac{n}{(n-2)!}\right]+\mathbin{\color{#3D99F6}1}+e-2\phantom{ccccccccccccccccccccc}\color{#3D99F6}\text{by Telescoping series sum}\\ &=\sum_{n=2}^{\infty}\left[\dfrac{n-2+2}{(n-2)!}\right]+e-1\\ &=\sum_{\color{#3D99F6}n=2}^{\infty}\dfrac{n-2}{(n-2)!}+\sum_{n=2}^{\infty}\dfrac{2}{(n-2)!}+e-1\\ &=\sum_{\color{#D61F06}n=3}^{\infty}\dfrac{n-2}{(n-2)!}+2e+e-1=\sum_{n=3}^{\infty}\dfrac{1}{(n-3)!}+3e-1=4e-1\approx\boxed{9.873} \end{aligned}

Chew-Seong Cheong
Aug 18, 2017

S = n = 1 n 4 ( n + 1 ) ! = n = 1 ( n 1 ) 4 n ! = n = 1 n 4 4 n 3 + 6 n 2 4 n + 1 n ! = n = 1 n 4 n ! 4 n = 1 n 3 n ! + 6 n = 1 n 2 n ! 4 n = 1 n n ! + n = 1 1 n ! = 15 e 4 ( 5 e ) + 6 ( 2 e ) 4 e + e 1 See note. = 4 e 1 9.873 \begin{aligned} S & = \sum_{n=1}^\infty \frac {n^4}{(n+1)!} = \sum_{n=1}^\infty \frac {(n-1)^4}{n!} \\ & = \sum_{n=1}^\infty \frac {n^4-4n^3+ 6n^2-4n+1}{n!} \\ & = \sum_{n=1}^\infty \frac {n^4}{n!} - 4 \sum_{n=1}^\infty \frac {n^3}{n!} + 6 \sum_{n=1}^\infty \frac {n^2}{n!} - 4 \sum_{n=1}^\infty \frac n{n!} + \sum_{n=1}^\infty \frac 1{n!} \\ & = 15e - 4(5e) + 6(2e) - 4e + e - 1 & \small \color{#3D99F6} \text{See note.} \\ & = 4e -1 \\ & \approx \boxed{9.873} \end{aligned}


Note:

n = 1 1 n ! = n = 0 1 n ! 1 = e 1 n = 1 n n ! = n = 1 1 ( n 1 ) ! = n = 0 1 n ! = e n = 1 n 2 n ! = n = 1 n ( n 1 ) ! = n = 0 n + 1 n ! = n = 0 n n ! + n = 0 1 n ! = n = 1 n n ! + e = 2 e n = 1 n 3 n ! = n = 1 n 2 ( n 1 ) ! = n = 0 ( n + 1 ) 2 n ! = n = 0 n 2 + 2 n + 1 n ! = 2 e + 2 e + e = 5 e n = 1 n 4 n ! = n = 1 n 3 ( n 1 ) ! = n = 0 ( n + 1 ) 3 n ! = n = 0 n 3 + 3 n 2 + 3 n + 1 n ! = 5 e + 6 e + 3 e + e = 15 e \begin{aligned} \sum_{n=1}^\infty \frac 1{n!} & = \sum_{n=0}^\infty \frac 1{n!} - 1 = e - 1 \\ \sum_{n=1}^\infty \frac n{n!} & = \sum_{n=1}^\infty \frac 1{(n-1)!} = \sum_{n=0}^\infty \frac 1{n!} = e \\ \sum_{n=1}^\infty \frac {n^2}{n!} & = \sum_{n=1}^\infty \frac n{(n-1)!} = \sum_{n=0}^\infty \frac {n+1}{n!} = \sum_{n=0}^\infty \frac n{n!} + \sum_{n=0}^\infty \frac 1{n!} = \sum_{n=1}^\infty \frac n{n!} + e = 2e \\ \sum_{n=1}^\infty \frac {n^3}{n!} & = \sum_{n=1}^\infty \frac {n^2}{(n-1)!} = \sum_{n=0}^\infty \frac {(n+1)^2}{n!} = \sum_{n=0}^\infty \frac {n^2+2n+1}{n!} = 2e+2e+e = 5e \\ \sum_{n=1}^\infty \frac {n^4}{n!} & = \sum_{n=1}^\infty \frac {n^3}{(n-1)!} = \sum_{n=0}^\infty \frac {(n+1)^3}{n!} = \sum_{n=0}^\infty \frac {n^3+3n^2+3n+1}{n!} = 5e+6e+3e+e = 15e \end{aligned}

Sir, This conclusions are nice and i also had drawn out. :)

Naren Bhandari - 3 years, 9 months ago

I have found a general formula: n = 1 n m n ! = B m e \sum_{n=1}^\infty \frac {n^m}{n!} =B_m \cdot e where, B m B_m is the m-th Bell Number.

Mrigank Shekhar Pathak - 3 years, 5 months ago

Log in to reply

Yes, I discovered it after solving another problem.

Chew-Seong Cheong - 3 years, 5 months ago
Naren Bhandari
Aug 18, 2017

S = n = 1 n 4 ( n + 1 ) ! S=\small\displaystyle\sum_{n=1}^{\infty}\frac{n^4}{(n+1)!}

= n = 1 [ ( n 2 + 1 ) ( n 2 1 ) ( n + 1 ) ! + 1 ( n + 1 ) ! ] =\small\displaystyle\sum_{n=1}^{\infty}\left[\frac{(n^2+1)(n^2-1)}{(n+1)!} +\frac{1}{(n+1)!}\right] = n = 1 [ ( n 2 + 1 ) ( n 1 ) n ! + 1 ( n + 1 ) ! ] =\small\displaystyle\sum_{n=1}^{\infty}\left[\frac{(n^2+1)(n-1)}{n!} +\frac{1}{(n+1)!}\right] = n = 1 [ n 3 n 2 + n 1 n ! + 1 ( n + 1 ) ! ] =\small\displaystyle\sum_{n=1}^{\infty}\left[\frac{n^3-n^2+n-1}{n!} +\frac{1}{(n+1)!}\right]

= n = 1 [ ( n 3 n 2 ) n ! + 1 ( n 1 ) ! 1 n ! + 1 ( n + 1 ) ! ] =\small\displaystyle\sum_{n=1}^{\infty}\left[\frac{(n^3-n^2)}{n!} +{\color{#3D99F6}\frac{1}{(n-1)!} - \frac{1}{n!}} +\frac{1}{(n+1)!}\right]

= n = 1 [ n ( n 1 ) ( n 1 ) ! + 1 ( n 1 ) ! 1 n ! + 1 ( n + 1 ) ! ] =\small\displaystyle\sum_{n=1}^{\infty}\left[\frac{n(n-1)}{(n-1)!} +{\color{#3D99F6}\frac{1}{(n-1)!} - \frac{1}{n!}} +\frac{1}{(n+1)!}\right]

= n = 1 [ n ( n 2 ) ! + 1 ( n 1 ) ! 1 n ! + 1 ( n + 1 ) ! ] =\small\displaystyle\sum_{n=1}^{\infty}\left[\frac{n}{(n-2)!} +{\color{#3D99F6}\frac{1}{(n-1)!} - \frac{1}{n!} }+\frac{1}{(n+1)!}\right]

= n = 1 [ 1 ( n 3 ) ! + 2 ( n 2 ) ! + 1 ( n 1 ) ! 1 n ! + 1 ( n + 1 ) ! ] =\small\displaystyle\sum_{n=1}^{\infty}\left[\frac{1}{(n-3)!} +\frac{2}{(n-2)!}+{\color{#3D99F6}\frac{1}{(n-1)!} - \frac{1}{n!}}+\frac{1}{(n+1)!}\right]

= e + 2 e + 1 + ( e 2 ) = 4 e 1 = 9.873 =\small e + 2e +{\color{#3D99F6}1} + (e-2) = 4e -1 = \boxed{9.873}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...